2009
DOI: 10.1016/j.immuni.2008.11.014
|View full text |Cite
|
Sign up to set email alerts
|

A Low Interleukin-2 Receptor Signaling Threshold Supports the Development and Homeostasis of T Regulatory Cells

Abstract: SUMMARY The IL-2/IL-2R interaction is essential for Treg cell development and homeostasis. Here we show that expression of IL-2Rβ chains that lack tyrosine residues important for the association of the adaptor Shc and STAT5 in IL-2Rβ-deficient mice resulted in production of a normal proportion of natural Treg cells that suppressed severe autoimmunity related with deficiency in IL-2/IL-2R. These mutant IL-2Rβ chains supported suboptimal and transient STAT5 activation that upregulated Foxp3 to normal levels in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
243
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(264 citation statements)
references
References 53 publications
20
243
0
1
Order By: Relevance
“…Analysis of the human FOXP3-bound regions that were associated with differentially regulated genes identified a number of transcription factor motifs that appeared to co-occur with FKH motifs, including AP-1, Runx, NFAT, and STAT binding motifs. The cooccurrence of these motifs is consistent with known roles for these transcription factors in nTregs (18,(65)(66)(67)(68)(69) and, in the case of AP-1, NFAT, and Runx family members, with their known physical interaction with FOXP3 (18,20,23). Several of the other transcription factor family motifs that are overrepresented in these sequences, such as BCL6 and PRDF, also contain members known to have a role in T cells, such as BCL6, PRDM1/Blimp-1, and cmyb (70)(71)(72)(73).…”
Section: Discussionsupporting
confidence: 81%
“…Analysis of the human FOXP3-bound regions that were associated with differentially regulated genes identified a number of transcription factor motifs that appeared to co-occur with FKH motifs, including AP-1, Runx, NFAT, and STAT binding motifs. The cooccurrence of these motifs is consistent with known roles for these transcription factors in nTregs (18,(65)(66)(67)(68)(69) and, in the case of AP-1, NFAT, and Runx family members, with their known physical interaction with FOXP3 (18,20,23). Several of the other transcription factor family motifs that are overrepresented in these sequences, such as BCL6 and PRDF, also contain members known to have a role in T cells, such as BCL6, PRDM1/Blimp-1, and cmyb (70)(71)(72)(73).…”
Section: Discussionsupporting
confidence: 81%
“…Then, Foxp3 expression is considered as sufficient to maintain natural Tregcell suppressive function in the periphery. Recent data suggest that IL-2 is important to stabilize Foxp3 expression in peripheral Treg cells [18,30,31]. Our study places on firm ground the importance of continuous interactions with self in maintaining Treg-cell suppressive capacities in the periphery.…”
Section: Discussionsupporting
confidence: 60%
“…Indeed, decreased Foxp3 expression in the periphery causes defective suppressive function of Treg cells and their conversion into effector cells, which contribute to, rather than inhibit, autoimmune diseases [26,27,29]. Recent data suggest strongly that IL-2 may play a role in the maintenance of peripheral Treg-cell suppressive capacities by promoting sustained expression of Foxp3 [18,30,31]. In the present article, we show that continuous interactions with self are required for maintaining Treg-cell suppressive function in the periphery.…”
Section: Discussionsupporting
confidence: 52%
“…Notably many of the genes down-regulated in CD25 − Tfr cells, such as Klrg1, Itgae (CD103), Prdm1 (BLIMP-1), Il10, and Gzmb (Granzyme B), are IL-2-dependent (34). Together with the known importance of IL-2 receptor signaling in the development of KLRG1 + BLIMP-1 hi eTreg cells (17,34), this finding suggests that CD25 − Tfr cells have primarily lost the IL-2-dependent component of eTreg gene expression. We found that ASCL2 may have a role in the down-regulation of CD25; additionally, a recent report has demonstrated that IL-21 signaling in Tregs inhibits CD25 expression via BCL6 (44).…”
Section: Discussionmentioning
confidence: 99%